2017
DOI: 10.1002/gcc.22475
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods for telomere length measurement in whole blood and blood cell subsets: Recommendations for telomere length measurement in hematological diseases

Abstract: Different methods of telomere length measurement are used to identify patients with telomeropathies. In our lab, we established four different methods for telomere length measurement, terminal restriction fragment (TRF) analysis by Southern blot analysis, quantitative PCR (qPCR), quantitative telomere/centromere fluorescence in situ hybridization (T/C-FISH) and fluorescence in situ hybridization combined with flow cytometry (FlowFISH). The methods each have distinct properties and apart from this-according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…32 Overall, the range of correlation values was low in line with previous studies showing similar correlations between flow-FISH and MM-qPCR. [31][32][33][34][35] Bland-Altman analysis confirmed that the overall agreement between flow-FISH and MM-qPCR was poor. Mean ratios and limits of agreement (LoA) between flow-FISH and MM-qPCR were moderate, with an average of 0.28 kb (LoA, 3.71 to −3.42 kb; Fig.…”
Section: Correlation Between Flow-fish and Mm-qpcrmentioning
confidence: 80%
“…32 Overall, the range of correlation values was low in line with previous studies showing similar correlations between flow-FISH and MM-qPCR. [31][32][33][34][35] Bland-Altman analysis confirmed that the overall agreement between flow-FISH and MM-qPCR was poor. Mean ratios and limits of agreement (LoA) between flow-FISH and MM-qPCR were moderate, with an average of 0.28 kb (LoA, 3.71 to −3.42 kb; Fig.…”
Section: Correlation Between Flow-fish and Mm-qpcrmentioning
confidence: 80%
“…Despite promising results from epidemiologic studies, pronounced intra- and interindividual variability hamper a wider application of LTL measurements in clinical practice [ 22 , 26 , 143 ]. Limited comparability between methods and laboratories further compromises the utility of LTL measurements on an individual basis [ 144 , 145 , 146 , 147 , 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…Note that even in the state of robustness, damage can be already abnormally high (b) and resilience already abnormally low (c) al., 2014). Work is underway to establish an optimal "gold standard" assay for epidemiological studies (Behrens et al, 2017;Montpetit et al, 2014). At this stage, there is not enough evidence in the literature to consider measuring telomere shortening as a biological mechanism of aging or telomere length as a biomarker of biological aging.…”
Section: Of 21mentioning
confidence: 99%
“…Observational studies using these techniques have reported contrasting results, and longitudinal studies have revealed erratic changes over time, possibly due to large measurement error (Berglund et al, ; Bischoff et al, ; Eerola et al, ; Lin et al, ; Müezzinler, Zaineddin, & Brenner, ; Solomon et al, ). Work is underway to establish an optimal “gold standard” assay for epidemiological studies (Behrens et al, ; Montpetit et al, ). At this stage, there is not enough evidence in the literature to consider measuring telomere shortening as a biological mechanism of aging or telomere length as a biomarker of biological aging.…”
Section: Introductionmentioning
confidence: 99%